2010
DOI: 10.1155/2010/659167
|View full text |Cite
|
Sign up to set email alerts
|

Influence of growth conditions on hydrophobicity ofLactobacillus acidophilusandBifidobacterium lactiscells and characteristics by FT-IR spectra

Abstract: In this study we have found, that the values of cell surface hydrophobicity (CSH) ofL. acidophilusLA5 andB. lactisBb12 cells change in response to varied growth conditions – phase of growth, concentration or type of carbon source, presence of oxygen. An evaluation of FT-IR spectra using cluster and quantitative analyses revealed substantial changes of the chemical composition depending on the CSH level ofL. acidophilusLA5 andB. lactisBb12 cells. Decrease of the carbohydrate level was observed in proportion to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…Polysaccharides are believed to contrast cell aggregation and adhesion 23 , suggesting that a decrease of these compounds could be a strategy of B. breve DSM 20213 to improve the hydrophobicity and auto-aggregation of its cells when exposed to LA. Previously, Shakirova et al 24 reported an increase of cell surface hydrophobicity in relation to decreased carbohydrate levels in Bifidobacterium lactis Bb12.…”
Section: Resultsmentioning
confidence: 98%
“…Polysaccharides are believed to contrast cell aggregation and adhesion 23 , suggesting that a decrease of these compounds could be a strategy of B. breve DSM 20213 to improve the hydrophobicity and auto-aggregation of its cells when exposed to LA. Previously, Shakirova et al 24 reported an increase of cell surface hydrophobicity in relation to decreased carbohydrate levels in Bifidobacterium lactis Bb12.…”
Section: Resultsmentioning
confidence: 98%
“…An increase in the growth of B. longum during the lag phase and some morphological modifications as well as changes in the fatty acid profile have already been reported (Ahn et al, 2001), whereas, for B. animalis ssp. lactis Bb12, changes in the surface hydrophobicity and an increase in protein content in the presence of increased oxygen concentration was observed by Shakirova et al (2010) Other factors to be considered are that aerobic conditions decrease the production of exopolysaccharides in some bifidobacteria strains, such as B. longum (Ninomiya et al, 2009), and this can be considered negative, as exopolysaccharides are able to increase viscosity and confer a desirable texture to the fermented product (Salazar et al, 2009).…”
Section: Postacidification Oxygen Levels and Proteolysismentioning
confidence: 99%
“…The three strains of Lactobacillus (i.e., L. acidophilus , L. gasseri , and L. jensenii ) used by Boris et al [ 67 ] showed about 80% surface hydrophobicity. B. lactis Bb12 and L. acidophilus LA5 showed surface hydrophobicity with values between 61% and 75% [ 68 ]. B. pseudolongum CIDCA 531 expressed 85% surface hydrophobicity [ 69 ].…”
Section: Cell Adhesive Propertymentioning
confidence: 99%